Simulation of hard projectile impact on friction stir welded plate - Wang, Wei (Cranfield University, 2011)
A numerical simulation is conducted using LS-DYNA to simulate hard projectile impact on a friction stir welded (FSW) plate. As the hard projectile has a wide range of velocity, mass and shape, when referring to AMC 25.963(e) of CS-25, ―Fuel Tank Access Cover‖, the hard projectile can be defined as 9.5 mm cubic-shaped steel engine debris with an initial impact velocity of 213.4 m/s (700 ft/s). This preliminary study was to evaluate whether the fuel tank adjacent skin panel joined by FSW would pass the regulation. First, the geometry and Johnson-Cook material model of the FSW joint were developed based on previous experimental research and validated by comparison with the tensile test on the FSW specimen. Then the impact on an Aluminium Alloy 2024 (AA 2024) plate without FSW was modelled. The minimum thickness of a homogeneous AA 2024 plate which could withstand the impact from engine debris is 3 mm. Finally the impact on 3 mm thick AA 2024 FSW plate was simulated. The welding induced residual stress was implemented in the plate model. The impact centre was changed from the nugget zone to the thermo-mechanically affected zone, heat-affected zone and base material zone of the FSW joint. Penetration only occurred in the model with impact centre on the nugget zone. Additional simulation indicated that increasing the thickness of the FSW plate to 3.6 mm could prevent the penetration.
Keywords: LS-DYNA; hard projectile; impact; FSW; AMC 25.963(e); Johnson-Cook; material model; AA 2024; penetration